Superkritični fluidi kot medij za procesiranje in sintezo polimerov - Čuček, Denis (visokošolska dela, 2015)
In recent years, polyethylenes (PE) are widely used for the advanced anticorrosion protection of various metal constructions and devices, which are very interesting due to their chemical and physical properties. Their use in varnishes and powder coatings industry becomes desirable and widespread since major limiting factor of environmentally hazardous volatile organic compounds % VOCs % plays a crucial role. Lately, trend in the world and especially in Europe is directed towards green chemistry to acquire products of high commercial value with minimum content of volatile organic compounds by processing and products manufacturing. Carbon dioxide (CO2) represents an excellent alternative to conventional solvents over many years. In the first part of dissertation the preliminary researches for low- and high density polyethelynes have been done to provide a good groundwork for high pressure processing. In a broad review of scientific papers and literature, data have not been found or their quality and/or quantity didn't reach minimum expectations. The main aim of the first part of research is acquirement of solid-liquid (S-L) phase equilibria for polyethylenes, solubility and diffusivity of gas (fluid) CO2 in polyethylenes. The data obtained are essential for polyethylenes processing. Behavior and ability of processing polyethylenes in sub- and supercritical fluids (CO2, propane) have been investigated. The solid-liquid (S-L) phase equilibria of low-density polyethelyne (LDPE) and high-density polyethelyne (HDPE) have been investigated in presence of carbon dioxide (CO2) and propane. Measurements of phase transition were performed in range of pressure of 1%90 MPa. Solubility and diffusivity of carbon dioxide in polyethylenes were measured at temperature of 373 K and pressures up to 30 MPa with using a magnetic suspension balance (MSB). The solubility of the fluid in polyethylene is influenced by pressure and/or temperature, and causes swelling of material. As well, mass of the polymer increases with solubility of gas. Consequently, viscosity and melting temperature of polymers reduce. In presence of carbon dioxide, the melting point of LDPE is influenced by two competing effects: a solubilization of gas in polymer and hydrostatic pressure. Oppositely, in presence of propane the hydrostatic pressure was not as pronnounced as in the presence of CO2. The solubilization effect of propane prevails over competing effect of hydrostatic pressure. For HDPE, in whole pressure range of CO2 the effect of hydrostatic pressure prevails, while in propane the solubilization effect prevails over competing effect of hydrostatic pressure. For the polyethylenes investigated in propane, melting point decreases in average for 17 K compared to CO2 medium. From MSB data it can be seen that solubility of CO2 in polyethylenes increases with increasing pressure. The highest solubility was obtained for low-density PE and the lowest solubility was obtained for high-pressure PE. In the second part of dissertation we focused on research of new technique of synthesis of biodegradable polymer of poly(propylene fumarate) (PPF) in supercritical carbon dioxide (scCO2). PPF could be used for biomedical applications and is potential as cellular ingrowth implant (substitute for human bone). PPF could be used as material for controlled (healing) substance delivery as well. Particularly, we were interested in an idea, whether the synthesis of PPF in absence of catalysts in scCO2 is possible. It has been found out the scCO2 is an excellent medium for the chemical synthesis of PPF.
Keywords: bone grafit substitutes; bone tissue engineering; Disertacije; equilibria; fazna ravnotežja; magnetic suspension balance; magnetna suspenzijska tehtnica; polietilen; Polimeri; polyethylene; propan; proprane; Sinteza; subcritical carbon dioxide; subkritični ogljikov dioksid; supercritical carbon dioxide; superkritični ogljikov dioksid; tehologija kostnih nadomestkov; tkivno inženirstvo